Феномени здоров’я та здоров’язбереження молоді в контексті сучасних наукових поглядів - Малишева, Леся (My University, 2017)
У статті розглядається й уточнюється сутність понять: «здоров’я», «здоров’язбереження», які мають взаємообумовлювальний характер, значну кількість трактувань, тому й зміст їх постійно наповнюється різними смисловими відтінками, обумовленими новим досвідом ставлення людей до власного здоров’я. Встановлено передумови формування здорового способу життя, а також суб’єктивні та об’єктивні причини необхідності формування здорового способу життя у системі виховних цінностей сучасної молоді. The article considers and clarifies the essence of the concepts: «health», «health preservation», which have a mutually controversial nature, a considerable number of interpretations, and therefore their content is constantly filled with different emotional shades, conditioned by new experience of people's attitude towards their own health. The author noted that a broad and diverse interpretation of the notion of health leads to the emergence of certain difficulties in its understanding; numerous definitions are usually non-adjacent, and the very meaning of health becomes variable, variable, diverse and practically not fixed within its limits. Health is be considered as a harmonious combination of the integral state, only the integrity of physical, mental, social and spiritual health is achieved comprehensively; neither side is an end in itself. They interact, mutually enrich and serve the solution of one common task - the comprehensive and harmonious development of the individual. The preconditions for the formation of a healthy lifestyle, as well as the subjective and objective reasons for the need to form a healthy lifestyle in the system of educational values of modern youth in general and teachers in the post office of the school in particular. They are responsible to provide health-preserving character of the educational process of the institution of education on the principles of «health-saving pedagogy» as a pedagogical system, in the center of which the highest value is the health of each student.
Keywords: здоров’я; фізичне здоров’я; психічне здоров’я; соціальне здоров’я; здоров’язбереження; суб’єктивні та об’єктивні причини; оздоровча життєва позиція